Development of a Backend Architecture for an Online Mental Counselling Platform to Enhance Performance and Security - Misna Asqia (The Indonesian Journal of Computer Science, 2025)
The increasing demand for mental health services during the COVID-19 pandemic emphasizes the importance of developing a web-based psychological counselling platform. This study aims to create a robust backend architecture to support the functional and non-functional requirements of an online mental counselling platform. The backend plays a crucial role in managing business logic, data management, user authentication, counselling session settings, and integration with third-party services. The Research and Development (R&D) methodology was implemented through the steps of requirements analysis, architecture design, module creation, and performance and security testing. The backend was built with a layered architecture approach, ensuring optimal load management, information security, and scalability. The application of authentication features with JSON Web Token (JWT) provides an extra layer of protection for user data. System tests were conducted using Postman through three main scenarios. The initial trial showed a "User does not exist" error (code 400) when user data could not be found. The second test resulted in an "Incorrect password" (code 400) when the password entered was incorrect. The third trial showed that the login was successful with code 200 OK, issuing an access token to the user. These results demonstrate the stability and accuracy of the backend implementation in managing user validation. Research findings include the design of an Entity Relationship Diagram (ERD) for data management as well as the development of backend modules that support CRUD functions. This backend platform improves service efficiency, protects user privacy, and enables wider access, including to remote areas. This study makes a meaningful contribution to the innovation of technology-enabled mental health services, creating opportunities for further development in support of inclusive and sustainable digital psychology services.